Are all day 6 blastocysts inferior to day 5 blastocysts? A retrospective study comparing reproductive outcomes between day 5 and day 6 good quality blastocysts in various clinical scenarios - Pandit, Rubina; Malik, Sonia; Gutgutia, Rohit; Talwar, Sandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Day 5 (D5) blastocysts have a better reproductive outcome than Day 6 (D6) blastocysts in fresh cycle transfer. However, conflicting results were observed in frozen embryo transfers (FET), primarily due to presence of multiple confounding factors. The aim of study was to compare reproductive outcomes between D5 and D6 good quality blastocysts in FET in different clinical scenarios causing infertility - female, male, unexplained and combined (male and female) factors. Methods: This was a retrospective cohort study conducted at multiple chains of a private fertility center. A total of 16,996 D5 and 4,382 D6 good quality blastocysts were included. Clinical Pregnancy Rates (CPR), Implantation Rates (IR), Miscarriage Rates (MR) and Biochemical Pregnancy Rates (BPR) were compared in four different scenarios. Results: In female factor, D5 blastocysts have better CPR (60.85% vs 47.95%) and IR (47.15% vs 36.13%) compared to D6 blastocysts. Similar outcomes were observed in unexplained factors where D5 blastocysts had better CPR (59.64% vs 45.83%) and IR (45.63% vs 33.08%) than D6 blastocysts. In male factor, CPR (53.61 % vs 49.79%) and IR (40.12% vs 39.96%) were comparable between D5 and D6 blastocysts. Similar comparable rates were found in combined causes - CPR (51.26% vs 48.97%) and IR (39.45% vs 37.78%). Conclusions: Reproductive outcomes were better in D5 than D6 blastocysts in female and unexplained factors. The results were comparable in male and combined factors indicating that not all D6 blastocysts can be considered inferior to D5 blastocysts.